Hyperbilirubinemia in Neonates: Types, Causes, Clinical Examinations, Preventive Measures and Treatments: A Narrative Review Article - Sana ULLAH; Khaista RAHMAN; Mehdi HEDAYATI (Tehran University of Medical Sciences, 2016)
Background: Hyperbilirubinemia, or jaundice, is a life threatening disorder in newborns. It is a multifactorial disorder with many symptoms. Generally, the physiological jaundice is the most prevalent type however in some regions pathological jaundice is also common. This review article focuses on a brief introduction to jaundice, its types and causes, measuring the bilirubin level, clinical approaches towards hyperbilirubinemia, different precautionary measures for the parents of babies suffering from hyperbilirubinemia and different remedial therapeutic measures for its treatment. Methods: The main databases including Scopus, Pubmed, MEDLINE, Google scholar and Science Direct were researched to obtain the original papers related to the newborns' hyperbilirubinemia. The main terms used to literature search were "newborns' hyperbilirubinemia", "newborns' jaundice", "Physiological Jaundice" and "Patholigical Jaundice". The timeframe included the obtained articles was from 1952 to 2015.    Results: Neonatal jaundice due to breast milk feeding is also sometimes observed. Hemolytic jaundice occurs because of the incompatibility of blood groups with ABO and Rh factors, when the fetus and mother blood groups are not compatible and the fetus blood crosses the barrier of the umbilical cord before birth causing fetus blood hemolysis owing to severe immune response. Conclusion: Jaundice is easily diagnosable however require quick and on the spot treatment. If not treated properly, it leads to many complications. Currently the treatment options for jaundice include photo therapy, chemotherapy, and vaccinations.